Analisis Pengaruh Penggunaan Informasi Akuntansi dan Karakteristik Internal Pengusaha terhadap Produktifitas UMKM - Bawono, Icuk Rangga; Arofah, Triani; Ubay, Berlian Muhammad S. (2020)
This study aims to examines the effect of the use of accounting information and internal characteristics of entrepreneurs including accounting training, business scale and educational level toward productivity of SME’s. The use of accounting information and internal characteristics of entrepreneurs is measured by Likert scale and scale score. The sample of 94 respondents of SME entrepreneurs is selected from the population of all SME entrepreneurs in Banyumas Regency, using the quota sampling method. Analytical techniques use multiple regression to test the relationship between independent variables with dependent variables, after all all data has been valid and reliable through data quality test. The result of the test shows that business scale, educational level and accounting information use have significant influence to business productivity, while accountancy training variables have no significant influence to productivity of SME’s.